Al-Fahmu and grammar learning: An analysis of morphology learning methods in Al-Fahmu - Millah, Fanni Izzatul; Nurhamim, Nurhamim; Ubaidillah, Ubaidillah; Mu'izzuddin, Mochamad (Abjadia : International Journal of Education, 2025)
This research is motivated by the problem of learning qawaid. This problem is influenced by many factors, including the textbook. The al-Fahmu book or what is known as the al-Fahmu method is a Qawaid textbook that has been used at the Darussalam al-Fahmu Islamic Boarding School in Pandeglang and often conducts much training in various schools and universities. However, there are still few who conduct research related to the al-Fahmu book. Therefore, the purpose of this research is to analyze the qawaid learning method in the al-Fahmu book and its advantages and disadvantages. So this research uses descriptive qualitative methods with the type of literature research. Data collection techniques from interviews with al-Fahmu authors and al-Fahmu teachers and analyzed using data triangulation. The results found are Qawaid learning with al-Fahmu using the Qiyasiyah method. The advantages of using al-Fahmu are understanding the rules by comparing examples without memorization, rule formulas, using red color for important points, how to mengi-rob, and the formula for reading traditional Arabic text. However, it does not escape the shortcomings that are not equipped with arguments from Imrithi and Alfiyah so students do not know the origin of the rule which is a challenge in the yellow book reading competition. And some vocabulary words that have no meaning so it becomes difficult for students to understand, especially those who are beginners.